2017
DOI: 10.3390/met7110498
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Deformation Mechanism of a near β Titanium Alloy through Isothermal Compression

Abstract: This study investigated the hot deformation behavior of Ti-4Al-1Sn-2Zr-5Mo-8V-2.5Cr alloy through isothermal compression tests at temperatures from 780 to 930 • C with strain rates ranging from 0.001 to 1 s −1 . The flow stress decreases with a decreased strain rate and an increased temperature. A constitutive equation was established for this alloy and the dependence of activation energy on temperature and strain rate is discussed. We further proposed a processing map using the dynamic materials model. On the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The average values of three tested results were obtained, in order to reduce the error. The test results of displacement and force data were translated into the true stress-strain parameters by using Equations (1) and (2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average values of three tested results were obtained, in order to reduce the error. The test results of displacement and force data were translated into the true stress-strain parameters by using Equations (1) and (2).…”
Section: Methodsmentioning
confidence: 99%
“…Titanium has been widely applied in an amount of areas including transportation, automotive industries [1], petrochemical, and marine [2]. It is also popular in the aerospace field [3], including gas turbine engines, load-carrying airframes, and wallboards because of its high strength-to-weight ratio, good toughness, resistance to corrosion, excellent thermal stability, and strength [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Thermomechanical processing parameters have a significant impact on the changes occurring in the microstructure during deformation of the materials that show susceptibility to dynamic recrystallization (DRX) or dynamic recovery (DRV). The identification of these changes in the microstructure has been the aim of many studies in the field of constitutive and dynamic material modeling for describing the hot deformation behavior of both metallic materials and in particular β titanium alloys [7][8][9][10][11][12][13][14][15]. Xiao et al [7] investigated the hot deformation flow behavior of a Ti-55511 alloy during hot compression using dislocation density-based constitutive model as well as processing maps.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Lin et al [11] showed a comparative analysis of artificial neural network, Hensel-Spittel, and straincompensated Arrhenius-type models to describe the flow behavior of Ti-55511 titanium alloy. Fan et al [9] and Wu et al [12] described the deformation mechanisms of Ti-7Mo-3Nb-3Cr-3Al and Ti-4Al-1Sn-2Zr-5Mo-8V-2.5Cr alloys, respectively, based on processing maps and constitutive equations. Zhao et al [13] and OuYang et al [14] analyzed the deformation mechanisms of Ti-1023 alloy during hot compression at supertransus temperatures using activation energy and DRX kinetics model, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The SPD treatment used to obtain UFG titanium and its alloys, as well as the microstructure and physical and mechanical properties of these materials have been thoroughly studied [3]; however, research continues [5]. The mechanisms of plastic deformation and the fracture of titanium alloys under various combinations and profiles of thermal and mechanical stresses are being studied [6][7][8].…”
Section: Introductionmentioning
confidence: 99%